The Impact of Organizational Learning on Strategic Awareness through Human Resource Flexibility: An Exploratory Analytical Study in the Colleges of Education, Business and Economics, and Political Science at Mustansiriyah University / Baghdad / Iraq (International Journal of Financial, Administrative and Economic Sciences, 2025)
Through this research, the researcher aims to shed light on the concepts (organizational learning, strategic awareness, and human resource flexibility). These concepts represent exceptional importance in organizations today, due to the development of tools, methods, and techniques that have greatly contributed to enhancing strategic awareness. This can only be achieved through human resources, which are the cornerstone of organizational development and success, especially if the human resource management system is characterized by flexibility in receiving training and learning. The research was based on the question: Does organizational learning have an impact on strategic awareness? And does human resource flexibility have an impact as a mediator in enhancing this awareness? The research focused on testing the impact between the independent and dependent research variables, namely (organizational learning and strategic awareness), and then testing the impact between the two variables through the mediation of human resource flexibility. The researcher selected the Faculties of Education, Administration, Economics, and Political Science at Al-Mustansiriya University as the research field. The research community was represented by the college's faculty members, totaling (460) Techers. The researcher selected a random sample of (210) techers, representing (45%) of the total. From the research community, the hypotheses were tested using statistical programs (SPSS, AMOS) using a number of statistical methods, including Cronbach's alpha and McDonald's omega reliability coefficients, construct validity, arithmetic mean, standard deviation, relative importance, and linear regression coefficient.
Keywords: Organizational Learning; Human Resource Flexibility; Strategic Awareness